KECERDASAN BUATAN SEBAGAI MITRA DALAM PENILAIAN DAN EVALUASI PENDIDIKAN - Alim Hardiansyah; Rosmawati Harahap; Arnes Yuli Vandika (CV. ADIBA ASIHA AMIRA, 2024)
Artificial Intelligence (AI) has emerged as a transformative technology in various fields, including education. AI offers significant capabilities in analysing large-scale data, providing real-time feedback, and tailoring assessments to students' individual needs. The research method used literature. The results showed that the integration of AI in educational assessment requires a balanced approach that blends the analytical power of AI with human judgement. In conclusion, AI has the potential to increase the effectiveness and personalisation of educational assessment, but its implementation must be done with careful ethical considerations and focus on enhancing, not replacing, the role of educators in the evaluation process.